Comparing Some Physical Traits According to Performance Level of Soccer Players Aged 13 Years Old - Gamal, Mohammed (Journal of Physical Education, 2018)
Comparing Some Physical Traits According to Performance Level of Soccer Players Aged 13 Years OldThe importance of the research lies in special physical traits of soccer players and finding the appropriate tests and measurements for them. The researcher used the descriptive method. The subjects were 30 soccer players aged 13 years old who represent the national soccer center. The researcher selected a set of variables, applied the main experiment, collected the data and then displayed and analyzed the data using proper statistical operations. The researcher concluded that physical abilities have a great effect on the level of performance during matches. Finally he recommended paying attention to the physical aspects of soccer due to its great effect on performance level.Keywords: physical traits, tests, soccer, performance level.